Implementation of Student Worksheets with Android-Based on Natural Science Subject - Deni Setiawan; Erika Wahyu Nurani; Arif Hidayat (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This study was conducted cause the student's learning outcomes were less successful. Based on the Midterm Assessment (PTS) evaluation at SDN 2 Mojo, 27 students (25%) were incomplete. Based on the data, the lowest value is 40, and the highest value is 80. The research adopts the ADDIE model with Mollena and Januszewski's theories: analyze, design, development, implementation, and evaluation. Research gets the following results: 1) Student Worksheet with the android system for Natural Science learning activities with style material created using the Android Studio application, operating through the lollipop type android system; 2) Student Worksheets with developed android systems included in the criteria were very feasible; Assessment was carried out by material and media experts with an assessment of the presentation component 90%, while the feasibility of content with a value of 92%; 3) The student worksheet was effective as a learning facility in Natural Science learning. The average pre-test value was 55.57143, and the post-test with a value of 80.88571. The t-test results showed that tcount ≤ - ttable with tcount calculation of -14,463 less than the ttable, which was -1.995469, then Ho was rejected. N-Gain earned amounted to 0.569775. As a result, there was a difference in the value of Natural Science style material after using Student Worksheets or LKS android-based. Keywords: Student Worksheets, Natural Science Subject, Worksheets Andorid Based